PERBANDINGAN KOMPRES HANGAT DAN KOMPRES DINGIN TERHADAP NYERI INSERSI AVF PADA PASIEN YANG MENJALANI HEMODIALISIS - Atunnisah, Mira; Haris, Fahni; Widiyanto, Purnomo (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2025)
Chronic Kidney Disease (CKD) requires long-term hemodialysis therapy which often causes pain due to needle insertion in Arteriovenous Fistula (AVF). This pain can interfere with patient comfort and compliance with therapy. This study aims to compare the effectiveness of warm and cold compresses in reducing AVF insertion pain in hemodialysis patients. The study used a quasi-experimental pretest and posttest design without a control group with a case study approach. The study was conducted in the hemodialysis room of dr. Tjitrowardojo Hospital on April 28–May 10, 2025. Three respondents were selected purposively according to the inclusion criteria. The variables observed were the level of pain before and after the intervention using the Numeric Rating Scale (NRS). Warm (43°C) and cold (11°C) compresses were given for 10 minutes before the procedure. Analysis using paired sample t-test. Both interventions reduced pain, but cold compress was significantly more effective (p = 0.020) than warm compress (p = 0.130). Cold compress is more effective as a non-pharmacological method in reducing AVF insertion pain. This intervention can be considered by health workers because it is simple, inexpensive, and effective.